Ondersoekings in verband met bone (Phaseolus vulgaris) - Van Blommestein, J. A.(Johan Adam) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc. Agric.) -- Universiteit van Stellenbosch, 1945.